RELASI POLITIK DAN AGAMA DI TENGAH KETIDAKPASTIAN IDEOLOGI - Maskuri Maskuri (LP2M Universitas Ibrahimy, 2015)
Relation between religion and nation state is a term that often be a topic discuss in terms of political Islam, there is an opinion that the relationship between religion and the state are integrated as an entity, and the other say there is a mention that religion and the state it is only a mutualistic-symbiotic, in another context mentioned implementers. And the other side, the relationship between religion and the state is not at all related to each other that called secularist-liberalis. Religion should not intervene against the state, and vice versa. However, globalization makes politic loses its meaning as a tool in the struggle for the establishment of an ideal society. Thus, this paper is more emphasis on the relation between religion and the state in politic.